Incidence of neonatal hypertension from a large multicenter study [Assessment of Worldwide Acute Kidney Injury Epidemiology in Neonates—AWAKEN]. (August 2018) - Kraut, Emily J.; Boohaker, Louis J.; Askenazi, David J.; Fletcher, Jeffery; Kent, Alison L.
Abstract Background Hypertension occurs in up to 3% of neonates admitted to the Neonatal Intensive Care Unit (NICU), and is a potentially under-recognized condition. The aim of this study was to examine the incidence of documented and undiagnosed hypertension from the 24-center Assessment of Worldwide Acute Kidney Injury Epidemiology in Neonates (AWAKEN) database, and to assess risk factors for hypertension according to gestational age. Methods Diagnosed hypertension was documented if an infant had a discharge diagnosis of hypertension and/or discharged on antihypertensive medications. Undiagnosed hypertension was defined when infants did not have a diagnosis of hypertension, but >50% of the lowest mean, diastolic and systolic blood pressure recordings were >95th percentile for gestational age. Results Of the 2162 neonates enrolled in the study, hypertension was documented in 1.8%. An additional 3.7% were defined as having undiagnosed hypertension. There was a significant correlation with neonatal hypertension and acute kidney injury (AKI). Additional risk factors for neonatal hypertension were hyperbilirubinaemia, Caucasian race, outborn, vaginal delivery, and congenital heart disease. Protective factors were small for gestational age, multiple gestations, and steroids for fetal maturation. Conclusions Neonatal hypertension may be an under-recognized condition. AKI and other risk factors predispose infants to hypertension.